Felbamate loaded solid lipid nanoparticles: in vitro and in vivo evaluation - RAMANUJ PRASAD SAMAL,; PRATAP KUMAR SAHU, (International Journal of Pharma and Bio Sciences, 2019)
Felbamate is chemically a phenylcarbamate derivative with PEGylation and it is pharmacologically an antagonist of N-methyl-D-aspartate receptor (NMDA) receptors. It is used primarily as an anticonvulsant for the treatment of severe refractory epilepsy. It is slightly soluble in water with t1/2 of 4-6 hours. Felbamate loaded Solid Lipid Nanoparticles (SLN) have been developed using stearic acid as lipid, poloxameras surfactant, polysorbate 80 as cosurfactant by microemulsion technique. Prepared SLNs were evaluated for particle size, drug content, in vitro release profile, release kinetics, in vivo acute toxicity and in vivo bioavailability. It was concluded from the study that the formulation prepared with lipid concentration of 50 mg, surfactant concentration of 75 mg, co-surfactant concentration of 0.75 ml, aqueous phase volume of 5 ml, stirring speed of 400 rpm, sonication time of 30 minutes in 500mL beaker and volume of cold aqueous phase 30 ml has shown the improved in vitro physic chemical properties and hence have chose as the best formulation. The relative bioavailability of this formulation was found to be 9.69 times higher than plain suspension.